Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.24875/acm.20000003
|View full text |Cite
|
Sign up to set email alerts
|

La asincronía ventricular izquierda como resultado de la estimulación apical permanente por dispositivos en el ventrículo derecho

Abstract: La estimulación apical permanente del ventrículo derecho (VD) puede producir asincronía del ventrículo izquierdo (VI) desde los puntos de vista eléctrico y mecánico. Este fenómeno es efecto de una alteración de la activación normal del VI que lleva al deterioro de la función sistólica y la aparición de insuficiencia cardíaca y sus efectos deletéreos relacionados. Para el estudio de la asincronía eléctrica del VI se ha propuesto en fecha reciente el nuevo sistema electrocardiográfico no invasivo Synchromax, que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Compared with other physiological pacing techniques, HBAP is also simpler: it has a smaller learning curve, relies only on the radiological anatomy, and exposes the patient to a shorter fluoroscopy time. These advantages have been extensively discussed by our group of researchers and other authors [13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other physiological pacing techniques, HBAP is also simpler: it has a smaller learning curve, relies only on the radiological anatomy, and exposes the patient to a shorter fluoroscopy time. These advantages have been extensively discussed by our group of researchers and other authors [13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The CSI is a result of graphic and mathematical processing of the signal averaged by the cross-variation of such leads. For this analysis, Synchromax® uses measurement of electric current flow (volume and direction) and analyzes the coincidence of intrinsicoid QRS deflections, as previously published [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Pacing-induced cardiomyopathy (PICM) from chronic high burden RVP has varied in definitions across studies, with several different thresholds for drop in LVEF identified. Most widely used definition is drop in LVEF to less than 40%–50%, with an absolute drop in LVEF of at least 5%–10%, with 10%–20% of patients with normal LVEF speculated to develop PICM from chronic high burden RVP ( 16 19 ). Permanent RVP results in interventricular dyssynchrony, due to a change in the normal activation of the LV.…”
Section: Pacing-induced Cardiomyopathy and The Need For Resynchroniza...mentioning
confidence: 99%